PELATIHAN PENGEMBANGAN SUMBER DAYA MANUSIA MELALUI PELAYANAN PRIMA DAN PENYAJIAN MINUMAN BAGI MASYARAKAT SADAR WISATA DI DESA BATUAN, KABUPATEN GIANYAR - Sudiparwati, Putu Ayu; I Gusti Agung Febrianto; I Ketut Rusdianata; Setyowati Widuri; Ni Luh Suastuti; I Wayan Muliana; Ni Kadek Eni Juniari; Ni Putu Ariesta Budani; Putu Mira Astuti Pranadewi9; I Nyoman Gede Agus Jaya Saputra; Arcana, I Nyoman; I Nyoman Rinala; Lidjah Magdalena Massenga; I Wayan Pastini (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2025)
Batuan Tourism Village is one of the oldest villages in Bali and is renowned for the breadth of its traditional arts. Classified as a pioneer tourism village, Batuan possesses diverse tourism resources, including adequate road access, centers of mask, keris, and statue craftsmanship, historical temples, arts and cultural performances, nature-based attractions, ancient Balinese houses, agrotourism, restaurants, accommodation, souvenir kiosks, and institutional support in the form of a tourism awareness group (Pokdarwis) and a formal village tourism management body. As a pioneering tourism village, Batuan requires harmonized tourism development that not only expands physical infrastructure but also strengthens human resource capacity so that the community is prepared to respond to tourism growth. This community service program, implemented by the Food and Beverage Service Study Program of Bali Tourism Polytechnic, aimed to enhance the hospitality competencies of local residents, particularly in relation to excellent service. The intervention took the form of a two-day training program combining theoretical sessions and practical exercises on banquet service and beverage service, delivered by lecturers and supported by students. The activity is expected to generate benefits for the tourism-aware community in Batuan Village in the form of improved understanding of excellent service, increased awareness of the importance of hygiene and sanitation in service delivery, and strengthened practical skills in serving beverages.